The role of educational attainment and quality in U.S. regional variation in prevalence of dementia and CIND - Jennifer A. Ailshire; Mateo P. Farina; Heide Jackson; Katrina M. Walsemann (PLoS ONE, 2025)
There are striking disparities in dementia prevalence across regions of the U.S. Education is one of the most important risk factors for dementia. Level and quality of education varied geographically for older cohorts of U.S. adults, potentially contributing to regional differences in dementia prevalence. This study links historical state education quality data to respondents ages 65 and older in the Health and Retirement Study to determine the extent to which geographic disparities in dementia and cognitive impairment with no dementia (CIND) can be attributed to state-level measures of education quality. Older adults educated in states with better resourced education systems had lower prevalence of dementia (Relative risk ratio (RRR): 0.81; CI: 0.75, 0.87) and CIND (RRR: 0.89; CI: 0.84, 0.93), while those educated in states where more school funding came from state rather than local sources had higher prevalence of dementia (RRR: 1.12; CI: 1.01, 1.23) and CIND (RRR: 1.10; CI: 1.03, 1.16). Educational attainment does not explain the higher prevalence of dementia or CIND in the US South, but state-level education quality fully accounted for higher prevalence of dementia and CIND in the South. Finally, state-level education quality indicators were more strongly associated with dementia and CIND among those with less education These findings suggest education does in fact explain regional disparities in dementia and cognitive impairment, particularly between the South and other regions, but that it is the educational environment that matters more for geographic differences than educational attainment in these cohorts.